Integrasi AI dan Kimia Hijau dalam Perkuliahan Kimia Inovatif - Salis Maulida Arismika; Wawan Wahyu (Jurnal Tadris Kimiya, 2026)
This study aims to identify the challenges and potential applications of Artificial Intelligence (AI) and Green Chemistry in chemistry education and laboratory practices as innovative approaches to chemistry teaching. The research method uses a Systematic Literature Review (SLR) conducted by referring to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Fifteen peer-reviewed articles published in the last four years and indexed in Scopus were selected from several databases, including the Education Resources Information Center (ERIC) and the Multidisciplinary Digital Publishing Institute (MDPI). The review results show that an effective integration strategy needs to position AI as a pedagogical tool for cognitive scaffolding, an object of scientific evaluation, and a medium for academic reflection, while Green Chemistry needs to be positioned as a framework for assessing the efficiency, safety, and environmental impact of chemical processes. This integration requires strengthening lecturer capacity, utilizing AI as a cognitive laboratory, implementing hybrid assessments, and integrating AI ethics into the curriculum. Thus, the integration of AI and Green Chemistry not only contributes to learning innovation but also has the potential to transform Indonesian chemistry education to be more critical, reflective, ethical, and sustainable. It is suggested that these findings serve as a pedagogical framework for educators and policymakers in navigating the digital era.